1986
DOI: 10.1104/pp.80.2.369
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of Phosphoenolpyruvate Carboxylase from Immature Pods of Chickpea (Cicer arietinum L.)

Abstract: Phosphoenolpyruvate carboxylase (EC 4.1.1.31) was purified to homogeneity with about 29% recovery from immature pods of chickpea using ammonium sulfate fractionation, DEAE-cellulose chromatography, and gel filtration through Sephadex G-200 (9,22,23). In C4 plants, the enzyme levels in leaves are about 20-fold higher on a Chl basis than in C3 plants (9, 11) and the enzyme is localized in the cytoplasm of mesophyll cells (24). In addition to its role in C4 and CAM plants, relatively higher levels of PEP2 carbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Previous study has reported that, in addition to its role in C4 and CAM (crassulacean acid metabolism) plants, relatively higher levels of PEPCase have been found in pod tissues of several legumes. In these tissues, the enzyme has been suggested for reducing carbon losses by assimilating CO 2 released during dark respiration or photorespiration, in minimizing carbon losses and enhancing plant productivity and thus contribute to the carbon economy of the developing pods [68]. Legume seeds rich in proteins require a large supply of amino acids, for the synthesis of which carbon skeletons are derived from TAC.…”
Section: 4mentioning
confidence: 99%
“…Previous study has reported that, in addition to its role in C4 and CAM (crassulacean acid metabolism) plants, relatively higher levels of PEPCase have been found in pod tissues of several legumes. In these tissues, the enzyme has been suggested for reducing carbon losses by assimilating CO 2 released during dark respiration or photorespiration, in minimizing carbon losses and enhancing plant productivity and thus contribute to the carbon economy of the developing pods [68]. Legume seeds rich in proteins require a large supply of amino acids, for the synthesis of which carbon skeletons are derived from TAC.…”
Section: 4mentioning
confidence: 99%
“…The enzyme located in cytoplasm (5,8,14,16) catalyses reversibly the interconversions of Fru-6-P/Fru-1,6-P2 and PPi/Pi (Fru-6-P + PPi-Fru-1, 6-P2 + Pi) and has been partially purified and characterized from a number of nized in a prechilled mortar The purity of the enzyme preparation obtained from gel filtration through Sepharose CL-6B was judged by PAGE at 4°C in 7.5% gel, using Tris-glycine buffer (pH 8.3) as described earlier (21). Fifty ,ug enzyme protein were loaded onto the top of the gel and a current of 3 mA per gel tube was maintained throughout the process.…”
Section: Plant Materialsmentioning
confidence: 99%
“…In our earlier investigations, properties of two of the enzymes, viz. PEP carboxylase (22) and NADP+-malic enzyme (6), of the postulated sequence from chickpea pod wall were reported. We now describe the properties of partially purified NADP+-IDH from the same tissue.…”
mentioning
confidence: 99%